Peran Etika Profesi dalam Meningkatkan Kualitas Manajemen Pendidikan di Era Digital - Meriana, Sesi; Aulia, Nurul; Azril, Iman; Habib, Syafa’atul (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2025)
Digital transformation in the world of education has significantly changed the landscape of education management, both in terms of the role of educators, learning methods, and institutional management. Amidst this dynamic, professional ethics is a key element that determines the quality and sustainability of education management. This article aims to examine the strategic role of professional ethics in supporting adaptive, fair, and integrity-based education management in the digital era. Through a literature study approach, the discussion covers the role of ethics in decision-making, improving the quality of learning, strengthening student character, and efforts to maintain public trust in educational institutions. In addition, this article highlights ethical challenges in the use of digital technology, such as data privacy issues, the digital divide, and academic authenticity. Various strategies for implementing professional ethics values ​​are presented, such as strengthening organizational culture, developing ethics-based policies, ongoing training, an accountable monitoring system, and integrating ethics into performance assessments. The results of the analysis show that consistent application of professional ethics can create higher quality, humanistic, and competitive education governance in the midst of a complex digital era.